Electrocardiographic studies in brown swiss cows - Abdullah Başoğlu; Kürşat Turgut; Mahmut Ok; Ramazan Kadak (Eurasian Journal of Veterinary Sciences)
Electrocardiographic prameters in iotal 43 healthy Brown Swiss cow ranging in age from 4 to 8 years were measured, computed and analyzed. Electrocardiograms were recorded on a one-channel, portable electrocardiograph using bipolar limb, augmented unipolar limb and unipolar precordial leads. The electrocardiograph was calibrated at 20 mm per 1 mV and the paper speed was set at 25 mm per second. Electrocardiograms wera recorded twice in each cow within 15 days in the morning after feeding. The P, QRS, T waves and PQ, QT, ST intervals, as well as, the amplitud of the P, QRS, T waves were measured. The result of the study showed that the recording of bipolar limb, augmented unipolar limb and unipolar precordial leads varied from animal to animal, and in the same animal from time to time.